Effect of Priming in Enhancing Viability of Artocarpus heterophyllus Seeds - PUTHUSSERI SRUTHI,; NAVYA PATRICK,; JOS T PUTHUR, (Seed Research, 2026)
Recalcitrant seeds are the short lived ones, which do not survive drying and freezing during ex- situ conservation, thus their storage become problematic. Priming helps recalcitrant seeds of jackfruit (Artocarpus heterophyllus) to become more resistant to drought stress by enabling them to adapt with water deficiency during storage and thereby increase the viability. Two priming treatments - halopriming (using 75mM NaCl) and osmopriming (using 20% PEG) were imparted in jackfruit seeds, which counter the stress that develops in recalcitrant seed due to water loss. Moisture content and germination percentage of control and primed seeds decreased with increase in storage time. However, the decrease was much faster in control seeds under ambient conditions as compared to seeds stored after both the priming treatments. Priming in jackfruit seeds resulted in enhanced mitochondrial activity to overcome desiccation stress and also resulted in increased lipid peroxidation due to the effect of stress, imparted by the priming agents (NaCl and PEG). Concomitantly, primed seeds exhibited enhanced activity/content of enzymatic and non enzymatic antioxidants than in untreated seeds. indicating detoxify ROS operation by the well defined antioxidant machinery during desiccation or storage period. This resulted in the enhanced viability of primed seeds than control seeds as the desiccation stress imparted damages are repaired in the former. Because of the recalcitrant nature of jackfruit seeds, they are difficult to store and in this context, the extension of the viability period of jackfruit seed was an accomplishment, to achieve the storage of the same successfully.